A temporal shift in trophic diversity among a predator assemblage in a warming Arctic. Issue 10 (3rd October 2018) - Yurkowski, David J.; Hussey, Nigel E.; Ferguson, Steven H.; Fisk, Aaron T.
Abstract : Climate change is leading to northward shifts in species distributions that is altering interspecific interactions at low- and mid-trophic levels. However, little attention has been focused on the effects of redistributions of species on the trophic ecology of a high trophic-level predator assemblage. Here, during a 22-year period (1990–2012) of increasing sea temperature (1.0°C) and decreasing sea ice extent (12%) in Cumberland Sound, Nunavut, Canada, we examined the trophic structure of a near-apex predator assemblage before (1990–2002) and after (2005–2012) an increase in the availability of capelin—generally an indicator species in colder marine environments for a warming climate. Stable isotopes (δ 13 C and δ 15 N) were used in a Bayesian framework to assess shifts in diet, niche size and community-wide metrics for beluga whales ( Delphinapterus leucas ), ringed seals ( Pusa hispida ), Greenland halibut ( Reinhardtius hippoglossoides ) and anadromous Arctic char ( Salvelinus alpinus ). After 2005, consumption of forage fish increased for all predator species, suggesting diet flexibility with changing abiotic and biotic conditions. An associated temporal shift from a trophically diverse to a trophically redundant predator assemblage occurred where predators now play similar trophic roles by consuming prey primarily from the pelagic energy pathway. Overall, these long-term ecological changes signify that trophic shifts of a high trophic-level predator assemblage associated with climate change have occurred in the Arctic food web.